Genetic diversity studies among AAB group Indian banana cultivars using ISSR markers - K V Ravishankar; A Rekha; Rema Menon; C K Anoopa; K Sudeepa; R Poornima (Journal of Horticultural Sciences, 2017)
Banana and plantains are generally classified based on morphological characteristics namely AA, AAA, AB, AAB and ABB. Further, there are four sub-groups in AAB genomic group. Presently we analyzed diversity using ISSR markers in 18 cultivars of AAB genomic group along with two each of AA types and BB wild accessions for comparison. The results have shown that AAB cultivars form a separate group. Dendrogram analysis showed that the subgroups ‘Plantain’ ‘Silk’ and ‘Mysore’ were placed in between AA and BB type. Whereas ten cultivars of ‘Pome’ sub group of the cultivars were unique and was placed in a separate cluster. In this study using ISSR markers, we are able to identify the subgroups clearly and their genetic relationships within the AAB group. The cultivars Rasthali and Nendran were clearly separated. The Pome sub-group cultivars found to be in a group which may be based on their geographical origin.